Governing for a Healthy Population: Towards an Understanding of How Decision-Making Will Determine Our Global Health in a Changing Climate - Bowen, Kathryn J. (MDPI, 2011)
Enhancing the adaptive capacity of individuals, communities, institutions and nations is pivotal to protecting and improving human health and well-being in the face of systemic social inequity plus dangerous climate change. However, research on the determinants of adaptive capacity in relation to health, particularly concerning the role of governance, is in its infancy. This paper highlights the intersections between global health, climate change and governance. It presents an overview of these key concerns, their relation to each other, and the potential that a greater understanding of governance may present opportunities to strengthen policy and action responses to the health effects of climate change. Important parallels between addressing health inequities and sustainable development practices in the face of global environmental change are also highlighted. We propose that governance can be investigated through two key lenses within the earth system governance theoretical framework; agency and architecture. These two governance concepts can be evaluated using methods of social network research and policy analysis using case studies and is the subject of further research.